Overlooked and underserved: how healthcare fails men in the pursuit of equity - Schulz, Robert J; Ofner, Heidemarie; Nyirády, Péter; Rajwa, Pawel; Weiss, Julia; Shariat, Shahrokh F; Fazekas, Tamás (Current opinion in urology, 2025)
PURPOSE OF REVIEW: Men face distinctive health-related challenges as a result of biological, behavioral, and sociocultural factors. In addition, the modern healthcare system does not offer men equal opportunities and options to ensure sex-specific access and delivery to health services. Men's health concerns are, indeed, often not addressed or even forgotten. In this review, we wanted to assess the impact of biology and sociocultural effects on sex-specific life-expectancy. RECENT FINDINGS: Globally, men have a shorter life expectancy than women. With a 5.8 years gender gap in the USA and 5.4 in the EU-27 (both in 2022). Cardiovascular disease, cancer, and accidents continue to represent the primary causes of mortality for both genders with all having disproportional preponderance in men. In recent years, there has been a notable decline in age-adjusted mortality rates related to cancer, while there has been an increase in deaths from accidental and intentional self-harm. Moreover, in the United States, men are more likely than women to develop and die from nonsex-specific cancers. As a result, men's poor health affects productivity, absenteeism, and employment. SUMMARY: The status of men in healthcare is complex. It is rooted in history, culture, and institutions. To address disparities, we need a comprehensive approach that includes policy reforms, sociocultural changes, and a fair and equitable public discourse. Grassroots and top-down strategies are needed to ensure a value-based societal healthcare system acknowledging the unique health needs of men.
Keywords: Sex Factors; Spojené státy americké; Humans; disparity zdravotní péče; naděje dožití; Men's Health; dostupnost zdravotnických služeb; Female; Health Equity; rovnost ve zdraví; lidé; United States; Healthcare Disparities; Health Status Disparities; sexuální faktory; Health Services Accessibility; ženské pohlaví; Male; Delivery of Health Care; poskytování zdravotní péče; zdraví mužů; disparity zdravotního stavu; Life Expectancy; mužské pohlaví